Case Study of Onychomycosis Patients Treated with 1,064-nm Nd:YAG Laser - Rachel Bertolani do Espírito Santo (Case Reports in Dermatology, 2018)
Onychomycosis is the most frequent nail disease, with an estimated prevalence of 2–8%. Current treatment strategies include the use of oral and topical antifungals, despite low cure rates following these treatments. The objectives of this study were to assess the therapeutic response of patients with onychomycosis to 1,064-nm Nd:YAG laser treatment, the clinical evaluation method available for this therapy, and the possible side effects of this treatment. Twenty patients with onychomycosis underwent laser therapy. A total of 34 nails with onychomycosis were assessed according to the Onychomycosis Severity Index (OSI). This index generates scores that classify onychomycosis as mild, moderate, or severe. The OSI was determined before treatment and after a mean follow-up period of 8 months. The comparison between the initial and the final OSI for all 34 nails treated with laser therapy showed a significant difference; however, a low association was shown between these variables. A general reduction in the area of involvement and in the OSI numerical scores was observed. These data show a trend toward improvement in onychomycosis treated with 1,064-nm Nd:YAG laser. The OSI allowed an adequate clinical assessment of the response to laser therapy. Laser treatment did not cause marked discomfort in most patients, indicating that laser is a well-tolerated procedure.